We Judge Water Using our Senses in Surprising Ways. Issue 3 (1st March 2016) - Burlingame, Gary A.; Dietrich, Andrea M.
Abstract : Taste perceptions operate on subtle but powerful levels most of us aren't aware of. A closer look at the science behind best‐tasting water contests reveals the sensory complexity that determines our taste judgments.